2019
DOI: 10.1103/physrevresearch.1.033053
|View full text |Cite
|
Sign up to set email alerts
|

Multilayered vortices

Abstract: Vortices are localized planar structures that attain topological stability and can be used to describe collective behavior in a diversity of situations of current interest in nonlinear science. In high energy physics, vortices engender integer winding number and appear under the presence of a local Abelian symmetry. In this work we study vortices in a Maxwell-Higgs model, in which the gauge symmetry is enhanced to accommodate additional symmetries, responsible to generate localized structures to be used to con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 45 publications
(70 reference statements)
4
24
0
1
Order By: Relevance
“…The use of a field-dependent function coupled with the gauge field dynamical term has also been recently considered in [14] in the electric context, that is, in the presence of an electric charge fixed at the origin; there, we showed that the electric field has a behavior that captures the basic feature of asymptotic freedom, an effect that is usually associated to quarks and gluons. It was also considered, for instance, in [15][16][17][18][19] to describe vortex configurations with internal structures in the plane in the magnetic context. Moreover, very recently, in [20] the authors studied the dielectric Skyrme model, that is, the Skyrme model where both the kinetic and Skyrme terms are multiplied by field-dependent functions, leading to new results of current interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a field-dependent function coupled with the gauge field dynamical term has also been recently considered in [14] in the electric context, that is, in the presence of an electric charge fixed at the origin; there, we showed that the electric field has a behavior that captures the basic feature of asymptotic freedom, an effect that is usually associated to quarks and gluons. It was also considered, for instance, in [15][16][17][18][19] to describe vortex configurations with internal structures in the plane in the magnetic context. Moreover, very recently, in [20] the authors studied the dielectric Skyrme model, that is, the Skyrme model where both the kinetic and Skyrme terms are multiplied by field-dependent functions, leading to new results of current interest.…”
Section: Introductionmentioning
confidence: 99%
“…The field-dependent function can be used to modify the magnetic properties of the medium to study vortices, as in [7][8][9][15][16][17][18][19], but it can also be considered to modify electrical properties of the medium, as in [3,4] and in [14], for instance.…”
Section: Introductionmentioning
confidence: 99%
“…[34] to circumvent the Derrick-Hobart theorem [35,36]. Furthermore, such an approach already has been used in different contexts, e.g., Maxwell-Higgs [29,37], magnetic monopoles [38], and gauged CPð2Þ [30].…”
Section: The Modelmentioning
confidence: 99%
“…The particular case α ¼ 1 has been previously approached in different contexts as global defect structures [34], skyrmionlike configurations [39,40], massless Dirac fermions [41], magnetic monopoles [38] and vortices with internal structures [29,30]. On the other hand, arbitrary values of α were used to discuss the solutions into a multilayered structure [37]. Then, by assuming the superpotential (30), the BPS equation (27) results…”
Section: Some Scenarios With Internal Structuresmentioning
confidence: 99%
See 1 more Smart Citation